2017
DOI: 10.1055/s-0037-1599250
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Variable Femoral Morphology in Osteoarthritic Chinese: Are Prostheses Today Sufficiently Suitable?

Abstract: We aimed to retrospectively investigate the morphology of the resected surfaces of femurs in Chinese patients who underwent total knee arthroplasty (TKA) and to assess the suitability of contemporary femoral components. Measurements on three-dimensional reconstruction after virtual bone cutting were performed on 142 knees from Chinese TKA candidates. The anteroposterior (AP) and mediolateral (ML) dimensions, aspect ratio (ML/AP), and posterior condylar angle (PCA) were measured in the axial plane; the height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A prospective cohort study evaluated the safety and feasibility of early removal of drainage tube in primary fast-track TKA.Wound drainage was removed within 6–12 h after surgery. The procedure could drain the haematocele and reduce the risk of infection, without increasing the sense of pain, inflammatory reaction, limb swelling, and total blood loss.Removal of drainage tube was therefore safe and feasible within 6–12 h after surgery [192]. According to clinical expertise, drains can be avoided in selected cases, when local conditions free of obvious bleeding following re-established pressure ensure the absence of the risk of hematoma.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective cohort study evaluated the safety and feasibility of early removal of drainage tube in primary fast-track TKA.Wound drainage was removed within 6–12 h after surgery. The procedure could drain the haematocele and reduce the risk of infection, without increasing the sense of pain, inflammatory reaction, limb swelling, and total blood loss.Removal of drainage tube was therefore safe and feasible within 6–12 h after surgery [192]. According to clinical expertise, drains can be avoided in selected cases, when local conditions free of obvious bleeding following re-established pressure ensure the absence of the risk of hematoma.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this morphometric study has the largest sample size compared with other studies related to the distal femoral resected surfaces of OA knees in China. We believe that our data are more reliable 16–18,20,22,37 . Of course, this study has some limitations.…”
Section: Limitations and Strengthsmentioning
confidence: 63%
“…Zhang et al . found that a relatively higher underhang prevalence (51.4% of male and 38.3% of female patients) exists in males implanted with the Attune prosthesis 37 . While, Ho et al .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations